Is proprietary trading detrimental to retail investors? - Falko Fecht; Andreas Hackethal; Yigitcan Karabulut (Deutsche Bundesbank, 2013)
We study a conflict of interest faced by universal banks that conduct proprietary trading alongside their retail banking services. Our dataset contains the stock holdings of each and every German bank and of their corresponding retail clients. We investigate (i) whether banks deliberately push stocks from their proprietary portfolios into their retail customer portfolios, (ii) whether those stocks subsequently underperform, and (iii) whether retail customers of banks with proprietary trading earn lower long-term portfolio returns than their peers. We present affirmative evidence on all three questions and conclude that proprietary trading can, in fact, be very detrimental to retail investors.
Keywords: G30; G32; 330; conflict of interests; universal banks; proprietary trading; retail investment; retail banking